PENGEMBANGAN MODUL AJAR BANGUN RUANG SISI DATAR DENGAN METODE EXAMPLE NON EXAMPLES TERKAIT KEMAMPUAN BERPIKIR KRITIS - Asep Rahmat Maulana (Jurnal Dimensi Matematika, 2022)
This research is motivated by the low critical thinking ability of students in the mathematics learning process. One alternative learning that can be applied to improve students' mathematical critical thinking skills is the example non-examples method. The purpose of this study was to determine the validity of the teaching module, the effectiveness of the design of the teaching module, the practicality of the design of the teaching module, and to increase the response after using the example non examples method. The approach used in the research is a quantitative and qualitative approach. The method used in this research is the Design-Based-Research (DBR) development research method. The research subjects were all students of class VIII MTs Nur Rohmah Bandung City. The data collection instruments used consisted of formative tests, questionnaires, observation sheets, and teaching modules. In this study, quantitative and qualitative data were obtained. Quantitative data was obtained from the results of formative tests, while qualitative data was obtained from the results of observation sheets, questionnaires and teaching modules. The data analysis technique is done by looking at the average and percentage of the data. The results of the analysis concluded that the example non examples method had a positive impact on increasing students' mathematical critical thinking skills. In addition, students give a positive response to learning mathematics by using the method of non-examples.